Ship and Offshore Structure Design in Climate Change Perspective (2013)
This book summarizes results of longstanding research and scientific contributions from many projects and relevant working groups. It collects and evaluates wind and wave climate projections under changing climate having design needs and marine safety in focus. Potential impact of projected climate change in met-ocean conditions on ships and offshore structures is discussed and illustrated by an example of the expected wave climate change on tanker design.